Efektivitas Model Pembelajaran Treffinger Terhadap Berpikir Kreatif Siswa - Huni Apriatun Hasanah; Sukardi Sukardi; Hairil Wadi (Universitas Pendidikan Mandalika, 2022)
This study aims to analyze the effectiveness treffinger learning model affecting students' creative thinking in learning Sociology. The treffinger learning model has three essential advantages: understanding challenges, generating ideas and preparing actions that can improve students' creative thinking skills. This study was a semi-experimental study with a non-equivalent control group design. The sample consists of two classes: the experimental class and the control class. Data collection employed a description test that met the instrument's validity and reliability. All data were analyzed using a comparative test preceded by a requirements analysis test. The study revealed a difference in students' creative thinking between the experimental class using treffinger learning models and the control class with conventional learning models. Since the average score of the experimental class was higher, it is concluded that the treffinger learning model affects students' creative thinking. The theoretical implication is that using social reconstruction theory-based learning is relevant in the context of social learning.